INTERFERENCE AND CONTACT ANALYSIS OF SELF-ALIGNING BEARING IN LARGE ROLLING MILL BASED ON A SIMPLIFIED MODEL - ZHANG AnKang; DONG QingBing; CHEN Zhuang; LI JinChao; HE Dong (Jixie qiangdu)
The working conditions of self-aligning bearings in rolling mills are complex. The actual life of the bearing often does not reach the design life as expected. Therefore, it is of great significance to study the global load distribution and local stress distribution of self-aligning roller bearing. The global model involving contact of a number of elements often results in a long calculation time and convergence difficulty. Firstly, proposes a new simplified finite element model of bearing based on Hertz contact theory, which can greatly improve the calculation efficiency. Then, the roller contact loading distribution of the global model is solved based on the interference fit amount of the shaft and the inner ring of the bearing. Finally, the displacements corresponding to the maximum contact load is used as the boundary conditions of the local model, and the stress distribution of the inner ring is solved. The results show that the loading ratio of the two rows of raceways and loading distribution of the contact are varied with working conditions. The interference fit amount specified in the present study makes the minimum Mises stress of the inner ring greater than 40 MPa. This will reduce the strength and fatigue life of the bearing.